Development of an AKM-Based Chemistry Worksheet Integrated with Religious Values to Improve Students’ Learning Outcomes and Character in Hydrocarbon Learning - Dana Merina; Ayi Darmana; Nurfajriani Nurfajriani (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2026)
Background: Competency-based learning and character education are important priorities in contemporary chemistry education. However, instructional materials integrating Minimum Competency Assessment (AKM) and religious values are still limited, particularly in hydrocarbon learning.Aims: This study aimed to develop and evaluate an AKM-based chemistry worksheet integrated with religious values to improve students’ learning outcomes and character development.Methods: This research employed the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Participants were 60 eleventh-grade students from SMA Negeri 9 Medan, Indonesia. Data were collected through expert validation sheets, achievement tests, character questionnaires, and student response questionnaires. Data were analyzed using descriptive statistics, paired-sample t-tests, N-gain analysis, and Pearson correlation analysis with SPSS 26.Results: The developed worksheet demonstrated high validity, with expert validation scores ranging from 75% to 93%. Students’ learning outcomes improved significantly after implementation (t = -13.728, p < 0.001), and character development also showed significant improvement (t = -10.260, p < 0.001). In addition, students responded positively to the worksheet, with an overall response rate of 94%, categorized as very good.Conclusion: The AKM-based chemistry worksheet integrated with religious values was found to be valid, practical, and effective in improving students’ hydrocarbon learning achievement and character development.